Limited Sampling Strategy for the Estimation of Mycophenolic Acid and its Acyl Glucuronide Metabolite Area under the Concentration-Time Curve in Japanese Lung Transplant Recipients - Masaki Tanaka; Masafumi Kikuchi; Shinya Takasaki; Tensei Hirasawa; Kensuke Sigeta; Aoi Noda; Miki Akiba; Yasushi Matsuda; Hisashi Oishi; Tetsu Sado; Masafumi Noda; Yoshinori Okada; et al. (Journal of Pharmacy & Pharmaceutical Sciences, 2019)
Purpose: The dose of mycophenolate mofetil (MMF) used to prevent rejection after lung transplantation is often adjusted based on the 12-hour area under the concentration-time curve (AUC0-12) of mycophenolic acid (MPA). A limited sampling strategy (LSS) is useful to define the pharmacokinetic (PK) profiles of MPA and mycophenolic acid acyl glucuronide (AcMPAG). Therefore, this study aimed to design a LSS based on multiple linear regression for estimating the AUC0-12 of MPA and AcMPAG at the minimum blood sampling points in Japanese lung transplant patients with concomitant tacrolimus. Methods: Forty-five lung transplantation recipients were enrolled in a PK study of MPA, mycophenolic acid glucuronide (MPAG), and AcMPAG. The plasma MPA, MPAG, and AcMPAG concentrations were determined just before and at 0.5, 1, 2, 4, 8, and 12 hours after dosing. The AUC0-12 of MPA and AcMPAG was calculated using a linear trapezoidal rule from the plasma concentration of each blood sampling time. LSS was used to develop models for estimated AUC in the model group (n = 23) and was evaluated in the validation group (n = 22). Results: The best three time-point equation was 4.04 + 1.64·C1 + 3.08·C4 + 5.17·C8 for MPA, and -0.13 + 3.01·C1 + 3.51·C4 + 5.74·C8 for AcMPAG. The prediction errors (PE) and the absolute prediction errors (APE) were within the clinically acceptable ± 5% and 15% range, respectively (MPA: PE = 2.00%, APE = 11.66%, AcMPAG: PE = 0.98%, APE = 14.69%). The percentage of estimated AUC0-12 within ± 15% of the observed AUC0-12 was 77.27% for MPA and 81.82% for AcMPAG. Conclusion: LSS using three time-point (C1, C4, and C8) provides the most reliable and accurate simultaneous estimation of the AUC0-12 of MPA and AcMPAG in Japanese lung transplant patients.